Circle of Austria - Bonne, Rigobert, 1727-1794 (cartographer):::Creator::::::::::::; André, Gaspard (engraver):::Contributor::::::::::::; Desmarest, Nicolas, 1725-1825 (author):::Contributor:::::::::::: (Hôtel de Thou; Paris; France)
Map of Austria from the late 18th century